My Name : Slip of the Tongue, Somatic Anxiety, and its Strategy in English Speaking Class - Wijayanti, Farida Indri; Surtikanti, Monika Widyastuti; Lailiyah, Nur (Universitas PGRI Semarang, 2025)
The present study delves into the types of slip of the tongue occurring in formal speaking class accompanied by somatic anxiety and strategies to reduce it. The research employed a qualitative approach through students' observation of simulation, survey, and in-depth interviews. The participants were 91 students of the English language program joining the formal speaking class. The data were analyzed using the theory of slip of the tongue and the framework of somatic anxiety. The result revealed four types of tongue slips found in the formal speaking class: addition, substitution, perseveration, and repetition. The students with somatic anxiety produced more slip of the tongue than the non-anxious students. Substitution is the most dominant error produced by students. Most substitutions occurred due to the phonological similarity effect either in the mother tongue or in the target language. The findings also reported that the slip of the tongue was accompanied by somatic symptoms such as cardiopulmonary symptoms, musculoskeletal, gastrointestinal, and general symptoms. Students mostly experience cardiopulmonary symptoms palpitations, heavy sweating or perspiration, and nausea followed the symptoms. In addition, the internal factors that contributed to the slip of the tongue were fear of the stage, lack of confidence, and shyness factor. Finally, music therapy is perceived to be effective in alleviating the students' somatic symptoms and speech errors.